2016
DOI: 10.1083/jcb.201602010
|View full text |Cite
|
Sign up to set email alerts
|

Limited ER quality control for GPI-anchored proteins

Abstract: Sikorska et al. find that remodeling of a GPI anchor after its attachment to proteins inside the ER strongly promotes ER export but occurs independently of protein folding, thereby effectively limiting ER quality control, potentially including ER-associated degradation of all GPI-anchored proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 47 publications
0
53
1
Order By: Relevance
“…This behaviour is reminiscent of the fate of destabilized GPI‐APs in mammals and yeast that are not retained in the ER but are secreted and targeted to the lysosome for destruction. The molecular mechanism how abnormal GPI‐anchored proteins are preferentially directed to endosomes from the plasma membrane remains to be established (Satpute‐Krishnan et al ., ; Sikorska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This behaviour is reminiscent of the fate of destabilized GPI‐APs in mammals and yeast that are not retained in the ER but are secreted and targeted to the lysosome for destruction. The molecular mechanism how abnormal GPI‐anchored proteins are preferentially directed to endosomes from the plasma membrane remains to be established (Satpute‐Krishnan et al ., ; Sikorska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Such a process would seem to be the most efficient mechanism for disposal of misfolded VSG. However, in yeast and mammalian cells misfolded GPI‐anchored proteins are actually exported to the lysosome for degradation . This is because the GPI anchor is a forward trafficking signal for ER exit.…”
Section: When Good Vsg Goes Bad: Coping With Failed Antigenic Variationmentioning
confidence: 99%
“…However, in yeast and mammalian cells misfolded GPI-anchored proteins are actually exported to the lysosome for degradation. [46,47] This is because the GPI anchor is a forward trafficking signal for ER exit. This sets up a dynamic tension between retention by ER quality control versus packaging into secretory cargo transport vesicles À in these model organisms ER exit is the winner.…”
Section: Just Right: How Do Trypanosomes Precisely Regulate Vsg Synthmentioning
confidence: 99%
“…These observations together with the recent RESET pathway description, led to the postulation that the presence of a GPI anchor might obstruct ERAD for sterical hindrance [20]. However, findings from Sikorska and colleagues [23] demonstrated that the misfolded GPI-anchored protein Gas1* in yeast, is targeted to HRD1-dependent ERAD pathway, ruling out that a GPI anchor obstructs ERAD. Instead, the normally decreased ERAD for Gas1* is caused by remodelling of its GPI anchor (which occurs in all GPI-APs), thus proposing the new concept that the canonical remodelling of GPI anchor universally limits the ER quality control of GPI-APs.…”
Section: Quality Control Of Prpmentioning
confidence: 99%